Seasonal and tidal impact on the organic compounds and nutrients distribution in tropical mangroves, Kerala, India - R. GEETHA, N. CHANDRAMOHANAKUMAR and L. MATHEWS (Chemistry and Ecology Vol. 22, No. 1, February 2006, 29-45, 2006)
Seasonal changes in the concentration of nutrients and various organic compounds were studied in the waters surrounding mangroves and in the marshy areas of mangroves. Higher amounts of nutrients and organic compounds were observed during low tide. This is due to the remineralisation of plant detritus in this area. High concentration of carbohydrates, proteins, chlorophyll and phosphate were observed during monsoon, which can be attributed to the leaching of plant detritus as well as the land run-off. During pre-monsoon and post-monsoon high tannin and lignin concentration was noted. A 24-hour sampling was also done to study the tidal impact on the concentrations of various organic compounds and nutrients in this ecosystem. Even though a tidal impact was observed, a clear picture was not reported in this study.